PENANAMAN NILAI – NILAI NASIONALISME DALAM PENDIDIKAN PONDOK PESENTREN MIFTAHUL ULUM UNGARAN TIMUR KABUPATEN SEMARANG - Nur Rois (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2017)
Nationalism is a concept that lays the highest loyalty of a person to a country or can also beinterpreted that nationalism is an awareness of the basic inequality between colonizers andthe colonized. The value of the value of nationalism in Indonesia is essentially a perspectiveof the values of Pancasila. The cultivation of the values of nationalism is comprehensive forall societies including the institutions or institutions included in it. One of the non-formaleducation institutions in Indonesia that is recognized by the government is a boardingschool.The results of this study indicate that the meaning of cultivation of values of nationalism inthe sphere of daily life in Pondok Pesantren Miftahul Ulum Susukan Kab. Semarang isproven through activities such as Pengajian Kitongan Bandongan, Bahtsul Masa'il, jointco-operation, cooperative activities, joint discussions, consultations, and scout trainingactivities followed by santri men's groups. The determinant factor in the inculcation of thevalues of nationalism within, the scope of daily life in Pondok Pesantren Miftahul UlumSusukan Kab Semarang, among others, the role of teachers as motivators and facilitators,motivation from within students to study nationalism, interaction with the community, andfacilities and infrastructure which supports. Obstacles encountered in the cultivation ofvalues of nationalism in the daily life in Pondok Pesantren Miftahul Ulum Susukan KabSemarang includes the role of teachers as motivators and facilitators have not beenimplemented maximally, lack of motivation to learn from students, lack of interaction withthe community around the cottage, and Limited facilities and infrastructure.Keywords: nationalism, the values of nationalism, and boarding school